Risk assessment in inoperable chronic thromboembolic pulmonary hypertension - Yaylali, Y.; Kilickiran-Avci, B.; Akbulut, M.; Basarici, I.; Meric, M.; Atahan, E.; Ongen, Z. (Oxford Univ Press, 2022)
[Abstract Not Available]